Standardization and revision of morphological structures terminology for Glyphocrangonidae (Decapoda: Caridea) - Rodrigues, Thaiana G. A.; Cardoso, Irene A. (Zootaxa, 2022)
Glyphocrangonidae includes 96 species in one genus, Glyphocrangon A. Milne-Edwards, 1881 and this genus was divided into four informal species groups. This family has a complex morphology with many ornamentations on the body. Some papers tentatively standardized the group’s nomenclature, but it still presents understanding problems as one structure being called of three distinct names, for instance. Here, we are standardizing the nomenclature of Glyphocrangonidae based on the homologous structures that describe the group.